An ontology-based approach for on-site integrated environmental and health and safety management - Gangolells, Marta; Casals, Miquel (Revista Ingeniería de Construcción, 2012)
This paper presents an innovative approach to implementing integrated environmental and health and safety management systems in construction companies. It focuses on the sub-system for operational control of on-site environmental impacts and health and safety risks. The high compatibility between the operational control requirements that are stated in ISO 14001:2004 and OHSAS 18001:2007 and the demonstrated interactions between environmental impacts and health and safety risks (Gangolells et al., 2009, Gangolells et al., 2010) led us to develop a domain ontology to build an integrated knowledge model for operational control at construction sites. The ontology-based approach that we have developed is strongly influenced by the methodology provided by Noy and McGuiness (2001) and models the key concepts and their relations in the domain in a structured, extendable, flexible, reusable and shareable way. The ontology-based approach is implemented through Protégé 3.4 beta and properly evaluated by means of competency questions, internal verifications and expert validation interviews. This paper represents the first attempt at representing, sharing, reusing and managing the knowledge related to on-site integrated operational control of environmental and health and safety incidences and lays the ground for overcoming some barriers that contractors must face when they implement an integrated management system.